Generation of a lamin A/C knockout human induced pluripotent stem cell line (ZJULLi007-A) via CRISPR/Cas9 - Dandan Liu; Jiaxi Shen; Zongkuai Yang; Hangping Fan; Hao Wang; Ping Liang; Tingyu Gong (Stem Cell Research)
Lamin A/C is a protein encoded by the LMNA gene and belongs to the nuclear lamina protein family. Mutations in the LMNA gene lead to several diseases: Emery-Dreifuss muscular dystrophy, familial partial lipodystrophy, limb girdle muscular dystrophy, dilated cardiomyopathy, Charcot-Marie-Tooth disease, and Hutchinson-Gilford progeria syndrome. In this study, a lamin A/C knockout human induced pluripotent stem cell line was successfully generated using the CRISPR/Cas9 genome-editing technology, which was confirmed with normal pluripotency and karyotype.